Anxiety Levels In Menopausal Women - Ima Sukmawati; Yuyun Rahayu; Elis Noviati (Science Midwifery, 2022)
Background: Menopausal women experience physiological and psychological changes. The effects of these symptoms are headaches, hair loss, muscle pain, vaginal dryness, insomnia, weight gain, anxiety, irritability, difficulty concentrating, nervousness, feeling worthless, stress, and even depression. Objective: to determine the level of anxiety about menopause in Benteng Ciamis Village. Methods: The study used a descriptive method by filling out a questionnaire. Results: It was found that of the 30 respondents in the category of severe anxiety, 23 respondents (76.7%). Economic factors, knowledge and lack of recreation are the biggest contributing factors to anxiety in mothers facing menopause. Suggestion: support is needed, especially from the husband so that the anxiety experienced by the mother can be overcome. Keywords: Anxiety level, Menopausal women